The Phytoplankton Community Exhibited Restored Species Diversity but Fragile Network Stability Under Potential Sustainable Aquaculture Approach of Marine Ranching - Dongqun Wei; Zeping Xie; Jialin Li; Diansheng Ji; Lin Qu; Baoquan Li; Xiao Wei; Song Qin (Journal of Marine Science and Engineering)
Mariculture is currently experiencing rapid growth in response to the rising global food demand, while simultaneously posing significant challenges to environmental issues, such as pollution stress and ecological degradation. To achieve a balance between ecosystem maintenance and seafood supply, marine ranching has flourished as a sustainable approach through the implementation of artificial reef construction, stock enhancement, and strategic releasing. However, few studies have evaluated the ecological impacts through a comparison of in situ survey data across geographical areas. Phytoplankton are vital organisms in marine ecosystems that function as essential indicators of seawater quality and biological diversity, reflecting environmental health and ecological sustainability. In this study, we investigated the species diversity, community structure, and co-occurrence network of phytoplankton based on 175 samples collected from 75 sites encompassing all 26 marine ranching seawater areas, along with their corresponding surrounding areas in Yantai’s coastal sea. A total of 112 species were identified across three phyla of diatoms, dinoflagellates, and chrysophytes; among them, diatoms dominated the community with a notably high proportion of 98.83%. Their diversity and structure exhibited significant variations across different seasons and geographic locations. Moreover, no preference was observed between the marine ranching seawater and the surrounding areas. Nevertheless, a co-occurrence network analysis demonstrated that lower values for average degree, clustering coefficient, and average path length were exhibited in marine ranching, indicating that aquaculture activities have reduced connectivity among potential interactions. Additionally, it showed reduced stability as indicated by the remaining nodes and the natural connectivity indices, regardless of the proportion of nodes removed. These findings illustrate that while marine ranching processes can mitigate species losses with maintaining phytoplankton community structure, they still alter association among species and reduce overall stability. This research recommends that scientifically informed expansion of marine ranching necessitates robust environmental monitoring datasets and systematic validation to ensure holistic sustainability.